An ethnographic documentary-participatory: "Natem, the sacred drink of the Shuar" - Hinojosa Becerra, M. (2015)
This research describes the ritual use of ayahuasca in Shaime, a Shuar community located in the Ecuadorian province of Zamora-Chinchipe. Through participant observation and semi-structured interviews with community authorities, local healers and ayahuasca consumers, the social and cultural consequences of using the beverage by community residents are discussed. The text examines the social changes in traditional medicine due to the development of government health programs in the community. This research shows that ayahuasca consumption is a key element that reinforces the cultural identity of community members, even among those who migrate to urban centres. Linking Shaime with the use of ayahuasca results in Natem, la bebida sagrada de los shuar (Natem, the sacred beverage of the Shuar), an ethnographic documentary shown at the World Ayahuasca Conference 2014